Unwritten rule : state-making through land reform in Cambodia - Beban, Alice, 1981- (Cornell University Press, 2021)
"This book investigates the importance of land in postconflict states through the study of a political campaign to develop land registration efforts inside agribusiness concessions in Cambodia"-- Provided by publisher.
Keywords: Land reform -- Cambodia.; Land tenure -- Political aspects -- Cambodia.; Power (Social sciences) -- Cambodia.; Nation-building -- Cambodia.; Réforme agraire -- Cambodge.; Pouvoir (Sciences sociales) -- Cambodge.; Reconstruction d'une nation -- Cambodge.; Propriété foncière -- Aspect politique -- Cambodge.; HISTORY / Asia / Southeast Asia; Land reform; Land tenure -- Political aspects; Nation-building; Power (Social sciences); Cambodia; Land titling, Cambodia and land, Land grabs, Land Conflicts, Post-conflict land reform.; Electronic books.